2020
DOI: 10.1029/2019jb018698
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Profiles Across the Crust‐Mantle Sections in the Oman Drilling Project Inferred From Dry and Wet Resistivity Data

Abstract: Permeability profiles in the crust‐mantle sequences of the Samail ophiolite were constructed based on onboard measurements of the electrical resistivity of cores recovered during the Oman Drilling Project. For each sample, we measured dry and brine‐saturated resistivity during the description campaign on the drilling vessel Chikyu. Owing to the conductive brine in the pore space, wet resistivity is systematically lower than dry resistivity. The difference between dry and wet resistivity is attributed to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Studies addressing this issue via study of low temperature peridotite weathering in the Samail ophiolite includes Kelemen and Hirth (2012), Malvoisin et al (2020), andYoshida et al (2020). More generally, fracture-related frequency, porosity, and permeability in serpentinized peridotites has been studied in OmanDP drill core samples by Katayama et al (2020Katayama et al ( , 2021.…”
Section: Post-emplacement Alteration Of the Mbo And Vicinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies addressing this issue via study of low temperature peridotite weathering in the Samail ophiolite includes Kelemen and Hirth (2012), Malvoisin et al (2020), andYoshida et al (2020). More generally, fracture-related frequency, porosity, and permeability in serpentinized peridotites has been studied in OmanDP drill core samples by Katayama et al (2020Katayama et al ( , 2021.…”
Section: Post-emplacement Alteration Of the Mbo And Vicinitymentioning
confidence: 99%
“…Based on a variety of different lines of reasoning, catchment-scale-, Hole-to-Hole scale-, single Hole scaleand core-sample scale-studies have found that permeability in peridotite hosted aquifers in the Samail ophiolite is >10 −14 m 2 near the surface, and ∼10 −14 to 10 −15 below ∼100 m, with considerable Hole to Hole variability in the depth of this transition within the MBO (Dewandel et al, 2004(Dewandel et al, , 2005Katayama et al, 2020Katayama et al, , 2021Lods et al, 2020).…”
Section: Past Studies Of Groundwater Composition and Hydrology In The...mentioning
confidence: 99%
“…Permeability of natural intact peridotite and serpentinite measured in laboratory are in the ranges of 10 −18 to 10 −22 m 2 ( 12 , 38 , 41 ) and 10 −14 to 10 −22 m 2 ( 63 ), respectively. Contrary, field-scale permeability may be larger for partly serpentinized peridotite in Oman ophiolite [i.e., 10 −14 to 10 −15 m 2 ( 47 , 48 )], which are mainly controlled by macroscopic fissures ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“… 61 and 62 ), Q reaction for brucite carbonation ranges from 4.0 × 10 −7 /s (room temperature, atmospheric CO 2 ) to 12 (200 °C, P CO2 = 1 MPa). As the permeability of intact serpentinite is typically on the order of 10 −14 to 10 −22 m 2 at the scale of a core sample ( 63 ), the Ψ-value of brucite carbonation ranges from 5 × 10 3 to 10 −12 , which indicates fracturing for most conditions ( Fig. 6 D ).…”
Section: Controls On Fracturing and Self-accelerated Fluid Flowmentioning
confidence: 99%
“…However, they show distinct isotopic compositions in both sites above and below a highly brecciated zone at ∼180 m in Hole BA1B and above and below an unconformity associated with a highly brecciated zone at ∼70 m in Hole BA3A (Figures 4c and 5c). Katayama et al (2020) showed that dunites from Hole BA1B have a higher permeability than the harzburgites, leading to higher and focused fluid flux within the dunites and channeling of fluids with different compositions depending on the location within the borehole. We propose that the observed changes in the carbon isotope composition reflect changes in the hydrology of the system and that the percolating fluid at the Wadi Tayin Massif is heterogeneous with variable contributions of biologically derived carbon.…”
Section: Recent Dispersed Carbonate Precipitationmentioning
confidence: 99%